Ekstrak buah Mulberry (Morus alba L.) sebagai agen pemutih kulit - Bajuri, Annisa Nur Oktavia (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
High oxidants in the body and exposure from the outside can have an impact on the skin. The skin can become darker and duller. This causes the use of bleaching agents to be increasingly used. Many whitening agents that are made from chemical raw materials are toxic so that breakthroughs in raw materials that are natural and safer are offered. The natural raw material that can act as a whitening agent is mulberry fruit. Mulberry extract is rich in phenol, arbutin, tannin, which works as an antioxidant and tyrosinase inhibitor in the formation of pigments in the skin.